On convexity of the robust freeway network control problem in the presence of prediction and model uncertainty. (April 2020) - Schmitt, Marius; Lygeros, John
Highlights: A robust counterpart of the Freeway Network Control problem is proposed. We take uncertainty in the fundamental diagram and future traffic demand into account. Under certain conditions, the robust problem admits a tractable, convex reformulation. We also propose a receding horizon control approach with robustness guarantees. Abstract: In the freeway network control (FNC) problem, the operation of a traffic network is optimized using only flow control. For special cases of the FNC problem, in particular the case when all merging junctions are controlled, there exist tight convex relaxations of the corresponding optimization problem. In practice, many parameters of this optimization problem are not known with certainty, in particular the fundamental diagram and predictions of future traffic demand. This uncertainty poses a challenge for control approaches that pursue a model- and optimization-based strategy. In this work, we propose a robust counterpart to the FNC problem, where we introduce uncertainty sets for both the fundamental diagram and future, external traffic demands and seek to optimize the system operation, minimizing the worst-case cost. For a network with controlled merging junctions, and assuming that certain technical conditions on the uncertainty sets are satisfied, we show that the robust counterpart of the FNC problem can be reduced to a convex, finite-dimensional and deterministic optimization problem, whose numerical solution is tractable.